Utilizing Edmudo to Teach Writing with GBA in The Blended Learning Platform - Rendhi Fatrisna Yuniar (Scope : Journal of English Language Teaching, 2023)
This conceptual paper provides a future study based on a strategy of utilizing Edmodo to teach writing with a genre based approach (GBA) in the blended learning platform. Innovation in English teaching and learning process, especially in writing skills in this rapid growth technology era becomes challenge for teachers. Lack of time allocation, students’ writing skill, and the attention of writing significance become the obstacles in teaching and learning process. However, teaching writing needs appropriate approach in order to have good capability in writing skills. This paper went on to analyze suitable approach in teaching writing. This paper consists of the stages of genre-based approach namely Building Knowledge of the Field (BKOF), Modeling of the Text (MOT), Joining Construction of the Text (JCOT), and Independent Construction of the Text (ICOT) will be implemented through face to face activity and online by taking the advantage of Edmodo. The classroom activity was conducted to provide students with the basic concept of writing while the online activity was carried out in addressing the issues of limited time allotment for English writing, lack of students writing skill, and writing process significance in learning English. The conceptual paper signifies to supplement literatures for academics as reference for their research. The result of this future research may provide information about utilizing Edmodo to teach writing with a genre based approach. It will also be relevant to teachers who have difficulty in teaching writing.